Evaluation of Three Techniques for Detection of Low-Level Methicillin-Resistant Staphylococcus aureus (MRSA): a Disk Diffusion Method with Cefoxitin and Moxalactam, the Vitek 2 System, and the MRSA-Screen Latex Agglutination Test - Felten, Annie (American Society for Microbiology, 2002)
Very-low-level methicillin-resistant Staphylococcus aureus (MRSA), or class 1 MRSA, is often misdiagnosed as methicillin-susceptible S. aureus (MSSA). We evaluated the performances of three methods for detection of low-level methicillin resistance: the disk diffusion method using the cephamycin antibiotics cefoxitin and moxalactam, the Vitek 2 system (bioMérieux), and the MRSA-screen test (Denka). Detection of the mecA gene by PCR was considered to be the “gold standard.” We also determined the sensitivity of the oxacillin disk diffusion method with 5- and 1-μg disks and that of the Oxascreen agar assay with 6 mg of oxacillin liter(−1) for detection of MRSA. We compared the distributions of MICs of oxacillin and cefoxitin by the E-test (AB Biodisk), and those of moxalactam by dilutions in agar, for MRSA and MSSA isolates. The 152 clinical isolates of S. aureus studied were divided into 69 MSSA (mecA-negative) and 83 MRSA (mecA-positive) isolates, including 63 heterogeneous isolates and 26 class 1 isolates (low-level resistance). The cefoxitin and moxalactam disk diffusion tests detected 100% of all the MRSA classes: cefoxitin inhibition zone diameters were <27 mm, and moxalactam inhibition zone diameters were <24 mm. The Vitek 2 system and the MRSA-screen test detected 94 and 97.6% of all MRSA isolates, respectively. The sensitivities of the 5- and 1-μg oxacillin disks were 95.2 and 96.4%, respectively, whereas that of the Oxascreen agar screen assay was 94%. All of the tests except the 1-μg oxacillin disk test were 100% specific. For the class 1 MRSA isolates, the sensitivity of the Vitek 2 test was 92.3%, whereas those of the MRSA-screen test and the disk diffusion method with cefoxitin and moxalactam were 100%. Therefore, the cefoxitin and moxalactam disk diffusion methods were the best-performing tests for routine detection of all classes of MRSA.